1985
DOI: 10.1679/aohc.48.305
|View full text |Cite
|
Sign up to set email alerts
|

The relative frequency and topographical distribution of somatostatin-, GRP-,APP-, glucagon-,5-HT-, and neurotensin-immunoreactive cells in the proventriculus of seven species of birds.

Abstract: Summary.The relative frequency and topographical distribution of proventricular endocrine cells were examined immunohistochemically in seven species of birds: common finch, pigeon, quail, chicken, duck, gull and kite. Gastrin releasing peptide (GRP), somatostatin-, avian pancreatic polypeptide (APP)-, glucagon-, 5-hydroxytryptamine (5-HT)-and neurotensin-immunoreactive cells were observed in this study. GRP-and somatostatin-immunoreactive cells were found in all species examined.All six kinds of immunoreactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…In contrast to those of several birds studied by Yamada et al (1985), data from this study show that GRP, Som, and nNOS all occasionally occur in the epithelial layer of the gastric glands of the proventriculus of the Houbara bustard. In addition, while the distribution of GRP in the proventriculus is similar to that of the pigeon, quail, chicken, gull, and kite it differs from that of duck and the finch.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to those of several birds studied by Yamada et al (1985), data from this study show that GRP, Som, and nNOS all occasionally occur in the epithelial layer of the gastric glands of the proventriculus of the Houbara bustard. In addition, while the distribution of GRP in the proventriculus is similar to that of the pigeon, quail, chicken, gull, and kite it differs from that of duck and the finch.…”
Section: Discussioncontrasting
confidence: 99%
“…The neurotransmitters present in endocrine cells include gastrin-releasing peptide, somatostatin, and neuronal nitric oxide synthase. Other studies have identified GRP and Som as the main neuropeptides present in endocrine cells of the avian proventriculus (Alumets et al, 1977;Yamada et al, 1985;Yamanaka et al, 1989). In addition, glucagon (Rawdon and Andrew, 1981), avian polypeptide (Alumets et al, 1978;Rawdon and Andrew, 1981), and neurotensin (Rawdon and Andrew, 1981;Usellini et al, 1983) have been identified in the chicken proventriculus.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In birds, the amygdaloid complex includes the nucleus posterior amygdalopallialis (PoA), the TnA, and the area subpallialis amygdalae (SpA), and has been linked to visceral and limbic functions because of its connections with the hypothalamus and caudal brain stem nuclei. A dense 5-HT innervation was found for limbic structures like the TnA, the parahippocampal area (APH), hippocampus (HP), and area septalis in pigeons, chicken, and quails (Yamada et al, 1985;Cozzi et al, 1991;Challet et al, 1996). Recently it was shown that injections of the 5-HT 1/2/7 receptor antagonist Metergoline and the 5-HT 1B/1D agonist GR46611 into TnA induced hypophagic responses, whereas the same treatment in the arcopallium intermedium (AI) resulted in a selective increase in water intake (Campanella et al, 2009).…”
Section: Discussionmentioning
confidence: 99%